2016
DOI: 10.1515/libri-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Law Students’ Information Literacy Skills and Attitudes Towards Environmental Protection and Environmental Legislation

Abstract: This paper presents the findings of a small-scale pilot study on law students’ information literacy skills and their ability to find information on environmental protection. Environmental issues are a growing concern today and numerous associations, organizations and individuals are waging an active world preservation campaign. The aim is to demonstrate social responsibility and consideration for future generations by reducing the “ecological footprint.” The aim of the research was to ascertain the law student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Environmentally sustainable library and information services have not been discussed or researched widely in the mainstream scientific literature (Chowdhury, 2012a, 2012b, 2012c, 2013, 2014a, 2014b, 2016; Jankowska and Marcum, 2010; Nolin, 2010; Spink, 1995, 1999). The library and information science community has also recognized environmental sustainability and green issues as important (Balog and Siber, 2016; Fourie, 2012; Hauke, 2015; Hauke, et al, 2013; Spodick, 2016). For example, the Environment, Sustainability and Libraries Special Interest Group (ENSULIB) of IFLA (2017) and the ALA’s Task Force on the Environment (TFOE) (ALA, n.d.) aimed at making libraries and the public aware of diverse environmental information sources, addressed and sought out solutions to green concerns and practices in libraries, and promoted awareness of environmental issues in the library community for fostering green library initiatives.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmentally sustainable library and information services have not been discussed or researched widely in the mainstream scientific literature (Chowdhury, 2012a, 2012b, 2012c, 2013, 2014a, 2014b, 2016; Jankowska and Marcum, 2010; Nolin, 2010; Spink, 1995, 1999). The library and information science community has also recognized environmental sustainability and green issues as important (Balog and Siber, 2016; Fourie, 2012; Hauke, 2015; Hauke, et al, 2013; Spodick, 2016). For example, the Environment, Sustainability and Libraries Special Interest Group (ENSULIB) of IFLA (2017) and the ALA’s Task Force on the Environment (TFOE) (ALA, n.d.) aimed at making libraries and the public aware of diverse environmental information sources, addressed and sought out solutions to green concerns and practices in libraries, and promoted awareness of environmental issues in the library community for fostering green library initiatives.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, a number of studies of administrators of libraries have been conducted on effective leadership (Aslam, 2018; Fagan, 2012; Fought and Misawa, 2016; Wong, 2017): emotional intelligence (Hernon and Rossiter, 2006; Kreitz, 2009): managerial skills (Hernon, 2011; Jordan, 2012; Martin, 2018; Sabzwari et al, 2017): and in all these studies the results show a similar pattern: library leadership skills and qualities can be developed such as creativity, flexibility and the ability to adapt to change, awareness and engage in all activities of professional practice, and develop concrete action plans. While these studies are useful to understand library administrators’ roles, duties, behavior and willingness to change, in addition, a recent study by Balog and Siber (2016) ascertained law students’ attitudes towards environmental protection; the result shows that students are fairly concerned about the protection of the environment but do not feel adequately informed about the issue.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students are fairly concerned about the protection of the environment and do not feel adequately informed about the issue (Balog and Siber, 2017). A review of preceding studies indicated that the state and pattern of environmental awareness among library patrons has not received appropriate research attention.…”
Section: Introductionmentioning
confidence: 99%
“… 1. Here is a list of the analysed publications in chronological order: Antonelli (2008); Koloskova (2013); Herrera-Morillas et al (2014); Ashmore et al (2016); Balog and Siber (2016); Ghorbani et al (2016); Čadovska and Tkalčić (2017); Dragaš (2017); Geißler and Schumann (2017); Akbulut et al (2018); Kebe and Podjavoršek (2019); Kraljević (2019); Reiter Grubišić (2019); Zdravje and Korotaj (2019). …”
mentioning
confidence: 99%